2011
DOI: 10.1111/j.1365-2672.2011.04996.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of enrichment media for improved PCR-based detection of V. cholerae and V. vulnificus from estuarine water and plankton

Abstract: Aims:  Pathogenic Vibrio spp., including V. cholerae and V. vulnificus, are commonly found along the estuaries of the south‐east United States; however, it is often difficult to recover these species directly from environmental samples. Pre‐enrichment assays are commonly used to improve the detection of pathogenic vibrios from environmental sources. Here, we evaluated a novel enrichment procedure using freshly collected and autoclaved natural estuarine water amended with 1% peptone (designated as estuarine pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Enrichment procedures can minimize the interference of the PCR inhibitors and increase the concentration of the target micro-organisms. Enrichment for 5-12 h was applied during the detection of Vibrio species from fish, fishery products, shellfish and water (Hossain et al 2011;Jeyasekaran et al 2011;Malayil et al 2011;Wong et al 2012). In this study, we extracted DNA from inoculated shellfish homogenates and sea water before and after enrichment for 5 h. Detection was possible in sea water samples before and after enrichment, but weak amplicons were observed in shellfish samples before enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment procedures can minimize the interference of the PCR inhibitors and increase the concentration of the target micro-organisms. Enrichment for 5-12 h was applied during the detection of Vibrio species from fish, fishery products, shellfish and water (Hossain et al 2011;Jeyasekaran et al 2011;Malayil et al 2011;Wong et al 2012). In this study, we extracted DNA from inoculated shellfish homogenates and sea water before and after enrichment for 5 h. Detection was possible in sea water samples before and after enrichment, but weak amplicons were observed in shellfish samples before enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…The limit of detection for V. cholerae (ITS region) was 10 copies per PCR reaction in the water enrichment and 65 copies per reaction in the plankton enrichments. We have previously shown that this method of enrichment followed by PCR can reliably detect as few as 5 CFU 100 ml −1 of estuarine water and 2 CFU 25 ml −1 of material from a plankton net tow (Malayil et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…are referred to as somatic antigen type-1/139 non-agglutinable strains (SANAS-1/139- Vc or non-serogoup agglutinating O1/O139 V. cholerae (NSA-O1/139 Vc ) (Chatterjee et al 2011 ; Sack et al 2003 ). The SANAS-1/139- Vc member does not possess cell surface polysaccharide and antigenic determinant for agglutinating somatic antgen type-1/139 as the name specifies, yet its members ( V. cholerae strains) (Shan et al 2022 ; Devi et al 2022 ; Malayil et al 2011 ) may be implicated in cholera outbreak case, wound, septicemia, gastro-enteritis and diarrhea. These Vibrio members have been in existence in the environment (water, plankton/sediment and fishes) since the discovery of the family Vibrionaceae in 1890 (Huq et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%